Microplastic Analysis of Consumed Mussels (Donax sp.) and Tofu Clams (Meretrix sp.) - Listianingrum, Tri Agus; Pratiwi, Fika Dewi; Kurniawan, Andri (Jurnal Kelautan dan Perikanan Terapan (JKPT), 2023)
Clams Donax sp. and clams Meretrix sp. are consumable shellfish that can be contaminated with microplastic pollutants because it is a filter feeder. The level of microplastic pollutants in the waters can endanger the safety of shellfish food and the health of consumers who consume them. This study aimed to analyze the type and abundance of microplastics in shellfish Donax sp. in Pekapor Beach, South Bangka and clams Meretrix sp. in Pasir Padi Beach, Pangkalpinang. The shell sampling method was carried out by Purposive Sampling. Microplastic analysis was carried out in the laboratory with 3 repetitions, using 20 individuals in each repetition of the shell type. Microplastic extraction was carried out by the digestion process H2O2 30%, flotation with the addition of 60 gr NaCl, filtration with paper whatman 41 and identification using microscope. The types of microplastics found were fiber, foam, fragments and films. Abundance of types of microplastic shells Donax sp. fiber of 0,75-1,85 particles/individual, fragments of 0,15-0,25 particles/individual, films of 0,05-0,10 particles/individual and foam of 0,05-0,10 particles/individual individuals whereas in clams Meretrix sp. fiber of 1,10-2,35 particles/individual, fragments of 0,15-0,40 particles/individual, films of 0,05-0,20 particles/individual and foam of 0,05-0,10 particles/individual individual. The total abundance of microplastics in shellfish Donax sp. is 1,00-2,30 particles/individual while shells Meretrix sp. is 1,35-3,05 particles/individual. It can be concluded that consumption of shellfish Donax sp. and clams Meretrix sp. which are sold in markets around Bangka Island have been contaminated with microplastics.